Eltrombopag for treatment of thrombocytopenia after autologous stem cell transplantation in children single center experience - Bayram, Nihan; Yaman, Yöntem; Özdilli, Kürşat; Nepesov, Serdar; Odaman Al, Işık; Elli, Murat; Anak, Sema (My University, 2025)
Introduction: Thrombocytopenia is a common clinical problem in cancer patients undergoing high-dose chemotherapy and autologous hematopoietic stem cell transplantation (HSCT). It can occur as prolonged isolated thrombocytopenia (PIT) or secondary failure of platelet recovery (SFPR) and may cause potentially fatal bleeding. However, data on the treatment of post-transplant thrombocytopenia is still lacking. Methods: We reported our practices involving 15 pediatric patients who received eltrombopag (ELT) treatment for PIT and SFPR after autologous HSCT. Results: The overall response was 78.5% (11/14), with 1 patient excluded due to noncompliance. The 12 surviving patients' median follow up was 699 days (range: 167 to 2250 d). Conclusions: Our study indicates the efficacy and safety of ELT for treating PIT and SFPR after autologous HSCT in pediatric patients. However, more studies are needed to confirm these findings in children.
Keywords: Autologous Stem Cell Transplantation; Eltrombopag; Thrombocytopenia